1995
DOI: 10.1007/bf00011335
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi induced alteration to root longevity of poplar

Abstract: Root longevity is an important element determining the fluxes of nutrients and carbon within terrestrial ecosystems. The effect of colonisation by an arbuscular mycorrhizal (AM) fungus on root longevity of poplar was determined using a minirhizotron camera to make direct observation of roots in situ in conjunction with image analysis. Significant influences of colonisation on the longevity of roots were observed with most colonised roots surviving for a shorter period than non-colonised roots : only 16% of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 16 publications
3
47
1
Order By: Relevance
“…No difference in root deaths (either cumulative or instantaneous) was observed over the duration of our study and overall deaths were few. By contrast, Hooker et al (1995) reported AM colonization decreased the longevity of fine roots of poplar. The influence of mycorrhizal colonization on root production and mortality rates is clearly complex and requires further investigation with a range of host plants and fungal taxa before any firm conclusions can be made.…”
Section: Root Proliferationmentioning
confidence: 92%
“…No difference in root deaths (either cumulative or instantaneous) was observed over the duration of our study and overall deaths were few. By contrast, Hooker et al (1995) reported AM colonization decreased the longevity of fine roots of poplar. The influence of mycorrhizal colonization on root production and mortality rates is clearly complex and requires further investigation with a range of host plants and fungal taxa before any firm conclusions can be made.…”
Section: Root Proliferationmentioning
confidence: 92%
“…They have helped improve our understanding of many aspects of root ecology, including production, longevity, phenology and distribution in a wide array of ecosystems (Aerts et al, 1992;Dubach and Russelle, 1995;Eissenstat and Caldwell, 1988;Pregitzer, 1992a, 1993a,b;Hooker et al, 1995;Kosola et al, 1995;Taylor, 1987;Upchurch and Ritchie, 1983). Within the past few years, the technology associated with minirhizotrons has advanced considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Induced resistance responses to microbial inoculants are well documented in plants grown in vivo (Benhamou et al 1996;Hunt and Ryals 1996;Kloepper et al 1997). Moreover, induction of stress resistance in plant propagules produced in vitro prior to transplanting is the primary target of several research groups attempting utilization of microbial inoculants in micropropagation (Hooker et al 1995;Nowak et al 1995;Balla et al 1997;Lazarovits and Nowak 1997;Murphy et al 1997;Wilhelm et al 1997).…”
Section: Introductionmentioning
confidence: 99%